PROBLEMS OF ENSURING SAFETY AT OPEN PITS IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on ensuring safety at coal mines through analysis at existing coal mining facilities. It also provides information on the Angren coal mine. It is shown that there are no precise methods for determining the location of fires in order to increase the efficiency of preventing spontaneous combustion by feeding such liquid compositions as water and clay pulp flowing down the soil of the reservoir. Measures have been proposed to suppress the centers of spontaneous combustion, nitrogen is being used more and more, the supply of which ensures the volumetric processing of the collapsed mass and allows to reduce the oxygen concentration in the goaf.